-3x-4+7x=-36

Simple and best practice solution for -3x-4+7x=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-4+7x=-36 equation:


Simplifying
-3x + -4 + 7x = -36

Reorder the terms:
-4 + -3x + 7x = -36

Combine like terms: -3x + 7x = 4x
-4 + 4x = -36

Solving
-4 + 4x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 4x = -36 + 4

Combine like terms: -4 + 4 = 0
0 + 4x = -36 + 4
4x = -36 + 4

Combine like terms: -36 + 4 = -32
4x = -32

Divide each side by '4'.
x = -8

Simplifying
x = -8

See similar equations:

| 4g-5=3g+9 | | 4(4x-5)=8x+5 | | (-11x-8)=9 | | y+0.4=0.6 | | f=1.8*50+32 | | 7n=4n-9 | | 0.75r=-24 | | 12x+2y=126 | | 3n-5=7m-21 | | -7[4x+2]=5[2x+1] | | 2x+3=5-6x | | 3(-3)-10= | | 7x+23=0 | | 2.7x=5.5x+k | | -5[x+2]=3[x+2] | | 3n^2+13n+10=0 | | 4x-12=22 | | 3u^2-9u+5=0 | | .14x+(.8(x-5))=.01(3x-4) | | 2x-6=7x+44 | | 4x^2+23x-72=0 | | 40=1.8c+32 | | 5(3-x)=6-2x+7-3x | | 7[u-8]=3[u+4] | | 3x+3-.125=-x+4 | | 90x^2-90x+225=0 | | 18=4w^2+w | | .2p-4=.4p | | 0.50x+0.20y=3.60 | | -4v+15=-14 | | H-21=52 | | 3x+3-.125=-2x+4+x |

Equations solver categories